The community in business : Strategic relationship between companies and environment and marketing (2014)
Community language is not unrelated to companies (Chaston & Mangles, 2001), which define their activities as a benefit for community through sales of products or services. They also use in the social responsibility activities (Kakabadse, Rozuel, & Lee-Davies, 2005; Korhonen, 2002) in the communitycorporation involvement (Burke, 1999) that adds value to the latter ones (Rochlin, & Christoffer, 2000, p.1) in regards to the social marketing (Whitcombe, 2009) aiming to the elimination of barriers that hamper the implementation of social programs (McKenzie-Mohr, 2000a, 2000b), or, with a strategic view, in regards to the shared value that benefits community and companies at the same time (Porter & Kramer, 2011). There are, of course, many other ways to incorporate such language in companies. Marketing activities constitute the interaction between the environment and the companies, which are self-centered during their operations. Such activities have had functional, transactional, competitive, mixed, integral, relational aspects, among others. The latter one is an example of the wide possibilities when making work a relationship beyond the commercial elements. The relational marketing is characterized by the emphasis given to the maintenance and improvement of the relationship with the customer (Berry, 1995; Payne & Frow, 2006). It is an individual relation that foster brand fidelity and new interactions between the two parts. Nevertheless, as it is not possible to create personal bonds in a massive ways, relational marketing is surpassed by its own goals and became a systematized mechanism of products promotion under the appearance of relation (see Juárez, 2011), where the basis is customer satisfaction; as it was a functional model (see Smalley & Fraedrich, 1995) but with a higher independence from the product.